(untitled) (International journal of artificial intelligence, 2026)
The article analyzes key concepts of foreign language acquisition and the development of reading comprehension skills at the B1 level according to the Common European Framework of Reference for Languages (CEFR). It examines behaviorist, nativist, cognitive, and sociocultural approaches, as well as major reading models - bottom-up, top-down, and interactive. Special attention is given to their practical significance in teaching reading at secondary and higher education institutions. The study’s novelty lies in systematizing these approaches for B1-level learners and providing methodological recommendations for developing cognitive and metacognitive reading strategies.